Monitoring and Evaluation (M&E) of Development Projects: Issues Facing Nepal - Sharma, Sharad (Economic Journal of Nepal, 2005)
M&E are, perhaps the least emphasized areas in development programs/projects implementation of Nepal, as reflected in the continuous low performance of the periodic plans themselves. This paper attempts to present an analysis of the methodologies used in whatever scanty exercise done in the area in the recent past and highlights their limitations due to the differences in the techniques of surveys and studies. Following this, an effort is made by the author to develop a comprehensive framework for an effective M&E of development projects. Particular emphasis is placed on the M&E of poverty reduction projects as the basic goals of the Tenth Plan as well as development of a methodology for the active role of local government in the process. Basic issues such as income measurement and other indicators to development are discussed along with highlights on the specific desirable characteristics and the robustness of the indicators. A proposed M&E arrangement for poverty reduction is presented from the central to the grassroots level. Relevant critical issues in data generation and use in M&E are discussed with specific emphasis on poverty reduction focused development projects including pro-poor strategies. An analytical framework is also presented on critical development performance issues, in general and for the meaningful public participation in M&E. Economic Journal of Nepal Vol.28(3) 2005 pp.127-148